America's war against global Jihad: past, present, and future - Nester, William R. (Lexington Books, 2018)
This book analyzes America's crusade against Jihadism. It addresses the successes and failures of Washington's counter-Jihadist strategy before and after September 11, and explores whether the United States should stay the course or cut its losses in Iraq, Afghanistan, and elsewhere